2008
DOI: 10.1002/for.1085
|View full text |Cite
|
Sign up to set email alerts
|

How efficient is the European football betting market? Evidence from arbitrage and trading strategies

Abstract: This paper assesses the international effi ciency of the European football betting market by examining the forecastability of match outcomes on the basis of the information contained in different sets of online and fi xed odds quoted by six major bookmakers. The paper also investigates the profi tability of strategies based on: combined betting, simple heuristic rules, regression models and prediction encompassing. The empirical results show that combined betting across different bookmakers can lead to limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 45 publications
6
43
2
Order By: Relevance
“…This is one arbitrage opportunity per 125 matches, or 0.8%. The frequency of intra-market arbitrage opportunities in our sample is higher than the value of 0.5% found by Vlastakis et al (2009) in their sample of 12,841 soccer matches covering 26 different countries. One reason of the higher percentage of arbitrage opportunities in our sample is that we compare the odds of ten different bookmakers, whereas Vlastakis et al (2009) include only five different bookmakers.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…This is one arbitrage opportunity per 125 matches, or 0.8%. The frequency of intra-market arbitrage opportunities in our sample is higher than the value of 0.5% found by Vlastakis et al (2009) in their sample of 12,841 soccer matches covering 26 different countries. One reason of the higher percentage of arbitrage opportunities in our sample is that we compare the odds of ten different bookmakers, whereas Vlastakis et al (2009) include only five different bookmakers.…”
Section: Resultscontrasting
confidence: 82%
“…By contrast, in the bookmaker market the payout ratio on a winning bet is tied to the initially taken odds and does not depend on subsequent price changes. Empirical studies that test the arbitrage condition in bookmaker betting discover some opportunities for arbitrage when the number of bookmakers analysed is sufficiently large (see Pope and Peel 1989;Dixon and Pope 2004;Vlastakis et al 2009). Alongside the traditional market settings, exchange betting has emerged in recent years as a novel market mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, the widening of the set, and the greater diversity, of bookmaker activity under consideration here might reasonably be expected to generate a significant increase in arbitrage opportunities. This observation applies equally when comparing our results with those of Vlastakis et al (2009) who investigated arbitrage opportunities among a population of five PTBs and one BBB. Their results revealed sixty three arbitrage opportunities across the aggregate group of six, which reduced to just ten within the group of five PTBs, though they caution that these results may underestimate actual arbitrage opportunities as their analysis considered only closing odds, which would deny identification of opportunities associated with earlier available price menus.…”
Section: Second Franck Et Al's Focus On the Matched Offers Between supporting
confidence: 72%
“…The optimization process presented in (4) to (9) reveals the existence of 545 arbitrage opportunities across the 2,132 (that is, in 25.6% of) matches in our sample. Notably, this figure is significantly higher than the results of earlier studies (Franck et al (2013), Vlastakis et al (2009)) a fact which may be explained by a combination of the methodology employed to identify opportunities in this paper and the range of bookmakers under scrutiny. The method employed here, as described above, offers a comprehensive and reliable identification of opportunities by embodying time precision regarding the co-availability of odds and by ensuring identification of opportunities throughout the duration of the market, rather than, as with both Franck et al The distribution of arbitrage opportunities across the different leagues is shown in Table 3 and the frequency with which each bookmaker's odds feature in the optimized portfolio are shown in Table 4.…”
Section: Arbitrage Opportunities Across Bookmakerscontrasting
confidence: 67%
See 1 more Smart Citation